2018
DOI: 10.3892/ol.2018.8967
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1294 inhibited oral squamous cell carcinoma growth by targeting c-Myc

Abstract: Oral squamous cell carcinoma (OSCC) is the predominant histological type of oral cancer. The 5-year survival rate of OSCC is only ~50%. c-Myc is a known oncogene and target gene in various cancer types, including OSCC. The presnet study revealed that c-Myc is one of the target genes of miR-1294. Results indicated lower levels of miR-1294 in OSCC tissues samples collected from 24 patients with OSCC. Notably, overexpression of miR-1294 inhibited proliferation and migration in OSCC cell lines and inhibition of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…In glioma, miR-1294 inhibited cell proliferation and contributed to chemosensitivity via directing TPX2 [23]. Similarly, it was also down-regulated in oral squamous cell carcinoma tissues and cells and acted as a tumor suppressor via inhibiting proliferation and migration through regulating c-Myc [24]. Notably, previous study reported the correlation between the down-regulation of miR-1294 and the poor prognosis of esophageal squamous cell carcinoma [25].…”
Section: Discussionmentioning
confidence: 99%
“…In glioma, miR-1294 inhibited cell proliferation and contributed to chemosensitivity via directing TPX2 [23]. Similarly, it was also down-regulated in oral squamous cell carcinoma tissues and cells and acted as a tumor suppressor via inhibiting proliferation and migration through regulating c-Myc [24]. Notably, previous study reported the correlation between the down-regulation of miR-1294 and the poor prognosis of esophageal squamous cell carcinoma [25].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we identified that PKM2, a new target gene of miR-1294, played key roles in miR-1294mediated actions in osteosarcoma cells. Moreover, the tumor-suppressing role of miR-1294 has been reported in other of tumors, such as gastric cancer, 8 esophageal squamous cell carcinoma, 19 epithelial ovarian cancer, 7 oral squamous cell carcinoma, 9 and glioma. 11 Uncontrolled growth, invasion, and metastasis are the main characteristics of tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…5 Increasing evidence shows that miRNAs play important roles in regulating cancer cell development. 6 Previous studies have demonstrated that miR-1294 is lowly expressed in multiple cancers, such as epithelial ovarian cancer, 7 gastric cancer, 8 oral squamous cell carcinoma, 9 osteosarcoma, 10 and glioma. 11 Forced expression of miR-1294 inhibits tumor cell growth and cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-1294 is considered a tumor suppressor in many cancers, such as clear cell renal cell carcinoma and oral squamous cell carcinoma. 14 , 15 Besides, miR-1294 can be sponged by circ_0005198 to participate in the mediation of circ_0005198 on the proliferation, apoptosis and metastasis of glioma. 16 In OS, Zhang et al found that miR-1294 could restrain the proliferation and invasion of OS cells, 17 which provided a basis for exploring the role of miR-1294 in OS.…”
Section: Introductionmentioning
confidence: 99%